Analysis of High School Students' Reasoning Ability in Solving Higher Order Thinking Skill Type Mathematics Problems - Ana Muliyana; Asido Saragih; Jaya Santoso (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2025)
This study investigates the mathematical reasoning abilities of high school students in North Sumatra who participated in the Del Mathematics and Science Competition (DMSC). Prior studies have revealed that students’ reasoning abilities are generally low; however, limited attention has been paid to their performance in competition-based settings. The purpose of this study is to assess the mathematical reasoning skills of students through higher-order thinking problems adapted from National Science Olympiad (OSN) materials. This research employed a qualitative descriptive method. The participants consisted of 25 high school students who reached the final round of the DMSC. The instrument used was a written mathematical reasoning test consisting of five essay questions. Students’ responses were analyzed using descriptive statistics, including mean scores and percentage values based on established scoring rubrics. The results showed that 18 students were categorized as having low reasoning ability and 7 students had a moderate level. The average reasoning score was 63.84%, which falls into the low category. Although students could perform calculations, most of them struggled with argument validation and logical explanation.The findings emphasize the necessity for educators to develop instructional strategies that foster students’ mathematical reasoning, particularly through approaches that stimulate higher-order thinking skills.